Pengaruh Pendidikan Literasi Keuangan Terhadap Perencanaan Keuangan Siswa Sekolah Muslim Santitham, Thailand Selatan. - Sofiyani, Putri; Saraswati, Henny; Hillalliyati, Najmi; Shumalee, Shakirin (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2024)
This research aimed to examine the influence of financial literacy and behavior on students' financial planning at the Muslim Santitham Foundation School. Adopting a quantitative method, questionnaires were used as the primary data collection instrument. A total of 100 students from Matthayom levels 4 to 6 were purposively selected as the respondents. The results showed that financial literacy had a positive and significant impact on students' financial planning skills. In contrast, financial behavior, while showing a positive effect, did not significantly influence their planning. Despite financial literacy not being explicitly integrated into the school curriculum, the students demonstrated a satisfactory understanding of the basic principles of personal financial management. This research addressed a critical gap by exploring how financial literacy contributed to shaping planning among students, particularly within a cultural context where discussing financial matters was relatively new.